PERANCANGAN SISTEM PAKAR UNTUK MENDIAGNOSA SECARA DINI PENYAKIT PADA ANAK BERBASIS WEB (Information Technology and Telematics, 2013)
Diseases causedby virusesare veryvulnerable placein childrenthatis causedby theimmune systemthat are in thechild's bodyhas not been establishedcompletely.Most oftheparentsare also oftendo notrecognize the symptoms ofthe diseaseonthe child's bodythat arisesdue tothe virus. An expert systemwas constructedto diagnosechildhood diseasescaused by viruses. Of an expert systemcanprovideinformation about the disease, its symptoms, andtreatment.Thisexpert systemusesforward chaininginference method. This expert systemcan determine thediseaseand itstreatment andinitial treatmentshould be done, based onthe symptomsthat were previously selectedby the user. It is expectedthis expert systemcanhelp parentsandeverypersonin understanding thekind ofchildhood diseasecaused bya virus. Keywords : expert system forward chaining, disease, children, virus.